Helical self-assembly of molecules in pseudopolymorphs of racemic 2,6-di-O-(4-halobenzoyl)-myo-inositol 1,3,5-orthoformates: clues for the construction of molecular assemblies for intermolecular acyl transfer reaction - Krishnaswamy, Shobhana; Gonnade, Rajesh G.; Shashidhar, Mysore S.; Bhadbhade, Mohan M. (Crystengcomm, 2010)
The crystal structure of racemic 2,6-di-O-benzoyl-myo-inositol 1,3,5-orthoformate (1) which underwent a facile intermolecular benzoyl transfer reaction in the solid state, revealed a helical assembly of molecules along the two-fold screw axis via O-H center dot center dot center dot O hydrogen bond bringing the electrophile (C=O) and the nucleophile (-OH) in close proximity along the helical axis. However, structurally related racemic 2,6-di-O-(p-halobenzoyl)-myo-inositol 1,3,5-orthoformates (bromo (2) and chloro (3)) produced triclinic dimorphs (both P (1) over bar) when crystallized from methanol and ethyl acetate. Molecules in either form did not assemble spirally (like 1), and instead exhibited a one-dimensional isostructurality, bridging O-H center dot center dot center dot O linked identical molecular strings via C-H center dot center dot center dot O interactions across the inversion center. However, the molecules of 2 and 3 assembled in a helical manner similar to 1 with inclusion of solvent molecules in the crystal lattice when crystallized from other common organic solvents. Remarkably, in all the solvates the host molecules formed strikingly similar helices around the crystallographic 2(1)-screw axis through O-H center dot center dot center dot O bond involving the -OH group and carbonyl oxygen of the equatorial C2-O-benzoyl group. Comparison of the crystal structure of dimorphs and the solvatomorphs revealed that the solvent molecules, which interact with the orthoformate-bridge, trigger the helix formation of the host. The difference in the crystal structures of solvatomorphs arises in the interlinking of the neighbouring helices, which creates voids of different sizes to accommodate the solvent molecules. All the solvates crystallized in the monoclinic system distributed over three different space groups P2(1)/n, P2(1)/c and C2/c. In the P2(1)/n system, the adjacent helices are linked via C-X center dot center dot center dot O contacts, in P2(1)/c via C-H center dot center dot center dot X (X Cl, Br) contacts and in C2/c via short X center dot center dot center dot X contacts (X = Cl). The helical organization achieved through solvent mediation and inclusion is of significance in creating molecular packing for intermolecular acyl transfer reactions in crystals.